Mangroves in Alas Purwo National Park, Indonesia: Diversity and Its Potential Carbon Services - Samsu Rijal, Seftiawan; Furqon, M. Tanzil; Kadhafi, Muammar; Supriatin, Febriyani Eka; Aprillianto, Riqki Yoga (Bogor Agricultural University, Indonesia, 2024)
Mangroves are important ecosystems that help prevent global warming by storing carbon. A study in Alas Purwo National Park aimed to identify the species diversity and estimate the market value of total carbon from each mangrove species. The study used field sampling and diversity indexes. The study found that the study area has high diversity, with Shannon-Weiner, Margalef, and Pielou's Indexes of H' = 2.276, J = 0.949, and R = 1.453, respectively. Rhizophora apiculata was the dominant species with Above-Ground Carbon (AGC) and Below-Ground Carbon (BGC) stocks of about 34.73 Mg C Ha-1 and an economic value of 1,605, the highest among other species. The results of this study can help improve our understanding of the role of mangrove characteristics for both ecology and the economy.